Simulation of the Concrete Containing Palm Oil Fuel Ash and Metakaolin in Terms of Mechanical Properties - LOW, YI YUN; YUSAINI, AIMAN IQBAL; OSMAN, MOHAMAD HAIRI; AHMAD JENI, MOHAMAD LUTHFI (Progress in Engineering Application and Technology, 2025)
This research investigates the compressive and split tensile strength of concrete containing Palm Oil Fuel Ash (POFA) and Metakaolin (MK) by using simulation method and validate with experimental data. This study aims to validate the Abaqus finite element analysis (FEA) results with experimental data, investigates the mechanical behaviour of concrete that contains MK as an additive and POFA as a partial cement substitute and identify the optimal mix design for enhanced strength by replacing cement with specific ratios of POFA and MK. The compressive strength, force-bearing capacity, and stress-strain behaviour of concrete mixes made with POFA and MK in different ratios were assessed. The trustworthiness of the model was confirmed by the results, which indicated that experimental data closely matched FEA predictions made with Abaqus. In contrast to the control mix, moderate replacement levels of concrete mix containing 5% POFA and 10% MK showed improved mechanical properties, however higher POFA concentration resulted in decreased strength and ductility. These results highlight POFA and MK’s potential as sustainable concrete substitutes, given that the ratios are properly adjusted. By showing how simulation and experimental approaches can work in tandem to assess performance, this study promotes the development of green building materials.